(untitled) (Research, Society and Development, 2021)
Steel bridges are normally subjected to random loads with different traffic frequencies. This way, steel bridges are structures of dynamic behavior and are subjected to fatigue failure process. After localizing and determine the amplitude of an existing flaw, its important predicts crack propagation and the convenient repair time. At this work, the fatigue crack propagation on steel beam bridges, has been studied under different spectrum of variable-amplitude loading. To study the fatigue crack growth was developed a computational code, using the Root Mean Square (RMS) and the Cycle-by-Cycle models. Different loads histories and initial crack length were considered input variables. This way was evaluating the dispersion of results of the expected structural life choosing different initial parameters.